Adsorption characteristics of cadmium onto calcite and its agricultural environmental relevance - Hyun Ho Lee (Heliyon)
Calcite (CaCO3), a common component of calcium-based fertilizers, has been recognized for its effectiveness as a cadmium (Cd) immobilization agent in the solidification/stabilization (S/S) method. This strategy is a widely used chemical remediation technique aimed at reducing the bioavailability and toxicity of Cd in contaminated soils. This study comprehensively evaluated the potential of calcite for Cd remediation through geochemical analyses, including adsorption isotherms, saturation index, ion concentration changes, and X-ray diffraction (XRD) analysis. Adsorption isotherm experiments indicated that Cd adsorption onto calcite aligns more closely with the Freundlich isotherm model, suggesting a heterogeneous surface with a maximum adsorption capacity of 1.56 mg g−1. Based on chemical states result, optimal conditions for CdCO3 precipitation with low Cd concentrations were identified at pH above 7.9. XRD analysis confirmed the formation of Ca0.67Cd0.33CO3 at higher Cd concentrations, indicating that chemisorption is the dominant immobilization mechanism. Additionally, variations in Ca2+ and CO32− concentrations supported the substitution of Cd for Ca on the calcite surface. These findings highlight calcite's potential as an effective material for Cd immobilization, providing valuable insights for the developing more sustainable soil remediation strategies.